Production of succinic acid from bread waste - Nurshakirin, Roslee (2014)
A study of utilising waste bread as a sole nutrient source for the production of a nutrient rich feedstock for the fermentative succinic acid production by Escherichia coli has been developed. Waste bread, contains of nutrients, has been hydrolysed into water solution and adjusted its pH was gelatinized by heating the mixture at temperature 97°C. Then, microbial fermentation performed using bread hydrolysis and fermentation medium. Fermentation was carried out in anaerobic flask by using 300 ml working volume. After fermentation at 37 °C optimum temperature of Escherichia coli growth and 10 % (w/v) of substrate concentration, the results of HPLC analysis showed that increase in fermentation time will increase succinic acid production. The highest succinic acid concentration was 0.0801 gIL at 60 hours. The effect of substrate concentration, temperature and pH were studied and optimized. The optimum conditions for the succinic acid fermentation using waste bread were using substrate concentration of 15% (w/v), temperature at 30 °C and pH 6.5.